2018
DOI: 10.1007/978-3-030-04315-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Situational Incompetence: The Failure of Governance in the Management of Large Scale IT Projects

Abstract: Information technology (IT) projects in the government (public) sector experience significant challenges. Despite decades of research, the adoption of formal methods, the use of external suppliers and packaged software, these remediation attempts have not appeared to have reduced nor mitigated the problems faced when the public sector undertakes large IT projects. Previous studies have examined the causes of IT project failure, in particular these have focused on factor analysis. A relatively limited number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been reported that software projects are plagued with high failure rates than other industries' projects [58]- [62]. Even today, the percentage of successful software projects is too low and a large number of software projects experience outright failure [63]. According to the recent Standish Group's CHAOS Report [64], 74% of the software projects studied between 2013 to 2017 failed to meet their scope, schedule, and budget.…”
Section: A Role Of Scope In Project Successmentioning
confidence: 99%
“…It has been reported that software projects are plagued with high failure rates than other industries' projects [58]- [62]. Even today, the percentage of successful software projects is too low and a large number of software projects experience outright failure [63]. According to the recent Standish Group's CHAOS Report [64], 74% of the software projects studied between 2013 to 2017 failed to meet their scope, schedule, and budget.…”
Section: A Role Of Scope In Project Successmentioning
confidence: 99%